2017
DOI: 10.3389/fncel.2017.00391
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Mitigates Acute Neuroinflammation after Spinal Cord Injury through Inhibiting NLRP3 Inflammasome Activation in Microglia

Abstract: The spinal cord injury (SCI) is a detrimental neurological disease involving the primary mechanical injury and secondary inflammatory damage. Curtailing the detrimental neuroinflammation would be beneficial for spinal cord function recovery. Microglia reside in the spinal cord and actively participate in the onset, progression and perhaps resolution of post-SCI neuroinflammation. In the current study, we tested the effects of methylene blue on microglia both in vitro and in a rat SCI model. We found that methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…This short note combines, (A) the 2015 and 2016 observations of Basiorka et al ( 14 , 15 ) and 2016 work of Sallman ( 16 )—all three reporting that NLRP3 inflammasome constitutes a final common effector node driving a core element of the pathophysiology of MDS with, (B) the 2017 data sets of Ahn et al ( 26 ) and of Lin et al ( 27 ) plus the 2018 report of Hao et al ( 28 )—all three reporting that the NLRP3 inflammasome can be inhibited by the century old drug MB.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This short note combines, (A) the 2015 and 2016 observations of Basiorka et al ( 14 , 15 ) and 2016 work of Sallman ( 16 )—all three reporting that NLRP3 inflammasome constitutes a final common effector node driving a core element of the pathophysiology of MDS with, (B) the 2017 data sets of Ahn et al ( 26 ) and of Lin et al ( 27 ) plus the 2018 report of Hao et al ( 28 )—all three reporting that the NLRP3 inflammasome can be inhibited by the century old drug MB.…”
Section: Discussionmentioning
confidence: 88%
“…Ahn et al showed that MB inhibited LPS stimulated increase in murine NLRP3 function ( 26 ). Lin et al showed that MB inhibited murine cord transection initiated NLRP3 activation ( 27 ). Hao et al showed that MB inhibited NLRP3 assembly and function in streptozocin murine model of diabetic retinopathy ( 28 ).…”
Section: Methylene Bluementioning
confidence: 99%
“…4). 23,33,35,37 These results, together with the fact that dark-rearing significantly slows the rate of central rod loss compared to cyclic light-rearing in C57BL/6J Pde6brd10 mice, further support the possibility that distinct mechanisms are responsible for rod degenera- Further analysis finds that the difference between mice fed normal chow versus N5MB chow was significant between male and female P50 dark-reared Pde6brd10 mice (horizontal line); in male mice this difference was not statistically distinguishable from zero, whereas it was in female mice (star). Together, these results show that the greatest impact on rod survival by N5MB chow is found in P50 darkreared female Pde6brd10 mice.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] MB has also demonstrated anti-inflammatory properties. 32,33 In addition, we tested Norgestrel, a synthetic progesterone, due to its ability to protect rods and cones from degeneration in cyclic light-reared Pde6brd10 mice, and its anti-oxidant and antiinflammatory properties. 23,[34][35][36][37][38][39]…”
mentioning
confidence: 99%
“…It also improves systemic vascular resistance and mean arterial pressure while decreases vasopressor requirements in septic shock [ 265 ]. It also demonstrates anti-inflammatory effects because it can inhibit NLRP3 inflammasome activation [ 266 ]. The drug is currently being tested in the context of COVID-19 in a few trials alone (NCT04376788; n = 15) or in combination with vitamin C and N -acetylcysteine (NCT04370288; n = 20).…”
Section: Miscellaneous Antiviral Agentsmentioning
confidence: 99%